PERANCANGAN APLIKASI AUGMENTED REALITY PENGENALAN CANDI NUSANTARA BERBASISANDROID - Nurhadi; Mulyadi; Andil Patrian (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
A temple is a building that has a high historical value, the temple is a real proof of the ancient society technology that is very wonderful because of the limitations of existing infrastructure and facilities capable of producing a magnificent building, tall, sturdy and at that time, on the lessons of IPS elementary school 5th grade elementary schools of the country 139/IV the city of Jambi, students learn about the temple building, sometimes teachers gave lessons to her age so that children sometimes don't understand because language teachers sometimes get carried away into sebayanya languages, to address the teachers use picture clippings temples are tacked to the Board in order to interest students in higher and more focused on learning, from problems the writers decided to conduct research by designing and producing Augmented reality application that makes it easy for students to know the shape of the temple which learned in 5th grade with the 3D object, then create the framework with formulate the problem, determine objectives, collecting data, analyzing the data, after which the system development was undertaken, the author of system development method used in this research is to use the model of the development of the Prototype. This research is expected to make it easier to grade 5 students in learning and recognize the shape of the temples of the archipelago by utilizing the technology of AR.